2010
DOI: 10.3168/jds.2010-3235
|View full text |Cite
|
Sign up to set email alerts
|

Use of individual cow milk recording data at the start of lactation to predict the calving to conception interval

Abstract: Milk recording data collected in 2,128 dairy herds in England and Wales between 2004 and 2006 were used to predict the calving to conception intervals. The average cumulative milk production was 8,200 kg. Conception (or not) within 5 intervals measured in days (20 to 60 d, 61 to 81 d, 82 to 102 d, 103 to 123 d, 124 to 144 d) was modeled as a function of milk yields and milk constituents at the start of lactation using multilevel discrete-time survival models. Milk yield, weight and percentage of fat, protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 34 publications
4
35
0
1
Order By: Relevance
“…La identificación y registros individuales permiten un seguimiento reproductivo y productivo por vaca, lo que favorece el resultado de la explotación y el desempeño reproductivo (19,20,21) . Por otro lado, abordar los retos de las tecnologías de gestión (Cuadro 3) permitirá a los productores avanzar en el diseño estratégico de la explotación con un enfoque innovador y competitivo (3,16) , ajustado al sistema, lo que es factible ya que el 95 % de los productores son propietarios de…”
Section: Pt Gestiónunclassified
See 1 more Smart Citation
“…La identificación y registros individuales permiten un seguimiento reproductivo y productivo por vaca, lo que favorece el resultado de la explotación y el desempeño reproductivo (19,20,21) . Por otro lado, abordar los retos de las tecnologías de gestión (Cuadro 3) permitirá a los productores avanzar en el diseño estratégico de la explotación con un enfoque innovador y competitivo (3,16) , ajustado al sistema, lo que es factible ya que el 95 % de los productores son propietarios de…”
Section: Pt Gestiónunclassified
“…Identification and individual records allow a reproductive and productive follow-up per cow, which favors the operational result and reproductive performance (19,20,21) .…”
Section: Tp Production and Commercializationmentioning
confidence: 99%
“…Consequently, milk fat:protein ratios (MFPR) have been used to identify cows at risk of disease and subfertility in the postpartum period (Grieve et al, 1986;Geishauser et al, 1998;Heuer et al, 1999). However, a recent population study found that MFPR were unreliable predictors of fertility (Madouasse et al, 2010a). However, because different milk FA have different origins, they are likely to yield more information about the metabolic status of a cow than a generalized milk fat measure (Bauman and Griinari, 2001;Bauman et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Milk yield was unchanged when RUP concentration in the diet was increased before calving (van Saun et al, 1993), but milk protein percentage increased from 2.96 to 3.18%. Further, large observational studies suggest that reproductive performance is improved in cows with high milk protein concentration (Moss, 2001;Buckley et al, 2003;Morton, 2004;Madouasse et al, 2010). Further, large observational studies suggest that reproductive performance is improved in cows with high milk protein concentration (Moss, 2001;Buckley et al, 2003;Morton, 2004;Madouasse et al, 2010).…”
Section: Introductionmentioning
confidence: 99%